A Computational Study of CoCrFeNiTi High Entropy Alloys: Phase Diagrams, Thermodynamics, and Mechanical Properties from CALPHAD and First Principles - Anis, Geraldine (AUC Knowledge Fountain, 2021)
High entropy alloys (HEAs) are multi-component alloys, which are often defined as those consisting of at least 5 principal elements with concentrations ranging between 5 and 35 atomic weight percent (at.%). Since their introduction by Yeh et al. and Cantor et al. in 2004, HEAs have been found to possess many important properties and have become prime candidates for several high-performance applications such as high-temperature and biomedical applications. Despite their multi-principal element nature, many HEAs favor the formation of solid solution phases as opposed to the intermetallic phases expected for such systems. This was originally only attributed to their high configurational entropy. However, as more studies emerged, it became evident that the stabilization of solid solution phases in HEAs is contingent on many interdependent factors in addition to configurational entropy. One of the main obstacles that hinder HEA research is the vast compositional space available for a given HEA system, especially when non-equiatomic compositions are considered. For that reason, computational methods such as the calculation of phase diagrams (CALPHAD) have become central to the HEA field as they allow the efficient exploration of this massive search space. In the present work, a systematic framework for pinpointing single-phase HEAs and studying their properties from first principles was developed. First, the CALPHAD method was used to construct extensive phase diagrams of four CoCrFeNiTi sub-systems, namely CoxCrFeNiTi2-x, CoCrxFeNiTi2-x, CoCrFexNiTi2-x, and CoCrFeNixTi2-x. CALPHAD was also used to calculate several thermodynamic quantities, including the mixing enthalpies and entropies of the alloys, which were related to the phase stabilities obtained in the phase diagrams. In all our analyses, a special focus was placed on the single face-centered cubic (FCC) solid solution phase and the different factors that underly its stabilization. From the generated phase diagrams, an alloy with the composition CoCrFeNi1.75Ti0.25 and single-phase FCC structure was selected for a computational characterization of its mechanical properties. A special quasirandom structure (SQS), which facilitates the modeling of random alloys, was used for studying the CoCrFeNi1.75Ti0.25 alloy. An 80-atom 5x2x2 FCC supercell was generated, and first principles density functional theory (DFT) calculations were used to determine its mechanical properties. Computational tensile stress-strain diagrams were computed for the alloy SQS as well as its individual constituent elements their ideal tensile strengths were determined. An analysis of the alloy and element elastic constants was also carried out using DFT. The determined elastic constants were used to calculate the bulk, shear, and Young’s modulus as well as the Poisson’s ratio. The calculated element properties were compared to available experimental data and were used to benchmark the methods and analysis techniques employed. The calculated properties of the alloy SQS were compared to their corresponding weighted elemental averages. The coupled CALPHAD-DFT approach adopted in this work provides a methodical study of the phase stabilities and mechanical properties of non-equiatomic CoCrFeNiTi HEAs. The developed framework can also be extended to other HEA systems.